Comparison of 68Ga-PSMA PET and mpMRI for prostate cancer local staging: a comprehensive review and direct meta-analysis - Jin, Xinyu; Cai, Yijie; Ren, Xiaolu (Frontiers in Oncology, 2024)
PurposeThis meta-analysis is conducted to evaluate the comparative diagnostic efficacy of 68Ga-PSMA PET vs. mpMRI in detecting local staging of prostate cancer(PCa).MethodsA comprehensive search was conducted in the PubMed and Embase databases to identify publications up to February 2024. The analysis included studies that evaluated the direct comparison of 68Ga-PSMA PET and mpMRI for local staging of prostate cancer. The reliability of the analyzed studies was evaluated using the QUADAS-2 tool.ResultsThe meta-analysis included 10 articles involving 505 patients, which revealed that both 68Ga-PSMA PET and mpMRI had similar sensitivities and specificities in detecting extracapsular extension(ECE) and seminal vesicle invasion(SVI). The sensitivities for ECE were 0.56 (95% CI: 0.41-0.71) for 68Ga-PSMA PET and 0.57 (95% CI: 0.43-0.71) for mpMRI, and specificities were both 0.84 (68Ga-PSMA PET 95% CI: 0.75-0.91, mpMRI 95% CI: 0.76-0.91).For SVI, sensitivities were 0.57 (95% CI: 0.46-0.68) for 68Ga-PSMA PET and 0.70 (95% CI: 0.60-0.80) for mpMRI, with specificities of 0.92 (95% CI: 0.86-0.96) for 68Ga-PSMA PET and 0.94 (95% CI: 0.89-0.98) for mpMRI. There were no notable variations in sensitivity or specificity between the two methods for detecting ECE and SVI (P = 0.89 and 0.93 for ECE, 0.09 and 0.57 for SVI).ConclusionsThis meta-analysis indicates that 68Ga-PSMA PET has similar sensitivity and specificity to mpMRI in local prostate cancer staging. Nevertheless, the limited study sample size calls for further, larger prospective studies to validate these findings.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=522438, identifier CRD42024522438.